The first review of the subgenus Ganychorus Haliday, 1835 (Hymenoptera, Braconidae, Brachistinae) in China - Lu, Qian-Yu; Chai, Hong-Fei; Achterberg, Cornelis Van; Tang, Pu; Chen, Xue-Xin (Zootaxa, 2025)
A key to twenty-five Chinese species of the subgenus Ganychorus Haliday, 1835 is presented. Fifteen new species are proposed (B. (G.) aurigineus sp. nov., B. (G.) castaneus sp. nov., B. (G.) comatoides sp. nov., B. (G.) ejuncidus sp. nov., B. (G.) fuscifemur sp. nov., B. (G.) isoruficornis sp. nov., B. (G.) latiacis sp. nov., B. (G.) longitergitus sp. nov., B. (G.) mystrus sp. nov., B. (G.) scutellatus sp. nov., B. (G.) shanxiensis sp. nov., B. (G.) shennongjiaensis sp. nov., B. (G.) signiferoides sp. nov., B. (G.) tricolor sp. nov., B. (G.) xueshanensis sp. nov.) and three species (B. (G.) diversicornis (Nees, 1835), B. (G.) kangauzi Belokobylskij, 1995, and B. (G.) sutchanicus Belokobylskij, 1995) are newly recorded from China.